Rapid application development of pharmaceutical database system / Fatin Natasya Shuhaimi ... [et al.] - Shuhaimi, Fatin Natasya; Saad, Nor Liza; Masrom, Suraya; Ramli, Roslinda (UiTM Press, 2020)
This paper provides insight into the design and implementation of a pharmaceutical management system. The primary aim is to demonstrate the rapid development method in developing the important system with Python development tool mainly for the graphical user interfaces and database management. Today, there exists several kinds of pharmaceutical management system have been reported in the literature, but most contents were highly focused on the system functionality and usability studies. The literature that reports on rapid development tools for the system is found to be very limited. Today, with the critical needs of information technology to support fast and accurate data management, the development of information or management system by inexpert users has been an important issue to many organizations. Therefore, this paper presents the system from the aspects of database and usability design and the easy implementation tool for the case of developing a pharmaceutical management system. Usability testing is also provided to show the users evaluation on the system.